Pengaruh Kualitas Produk Dan Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus Toko Nikimi Mart Tebo) - Iliyas Iliyas (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to determine the effect of product and service quality on customer satisfaction and to determine which product and service quality has the most dominant influence on customer satisfaction. The research method uses multiple linear regression with the F test, t test and determination test. The results of the study concluded that based on the F test (simultaneous) used to determine the significance of the effect of the independent variables (product quality and service quality) on the dependent variable (customer satisfaction) simultaneously. The results can be concluded, H0 is rejected and H1 is accepted. Product quality and service quality simultaneously have a significant effect on Nikimi Mart customer satisfaction. Based on the results of individual (partial) tests, it can be seen that the variable that most influences consumer satisfaction at Nikimi Mart is the variable service quality (X2). H0 is accepted and H1 is rejected, in other words, product quality partially has no significant effect on Nikimi Mart customer satisfaction and on the service quality variable (X2), H0 is rejected and H2 is accepted, in other words, service quality partially has a significant effect on Nikimi Mart customer satisfaction.